Cargo crowding at actin‐rich regions along axons causes local traffic jams. (12th February 2018) - Sood, Parul; Murthy, Kausalya; Kumar, Vinod; Nonet, Michael L.; Menon, Gautam I.; Koushika, Sandhya P.
Abstract : Steady axonal cargo flow is central to the functioning of healthy neurons. However, a substantial fraction of cargo in axons remains stationary up to several minutes. We examine the transport of precursors of synaptic vesicles (pre‐SVs), endosomes and mitochondria in Caenorhabditis elegans touch receptor neurons, showing that stationary cargo are predominantly present at actin‐rich regions along the neuronal process. Stationary vesicles at actin‐rich regions increase the propensity of moving vesicles to stall at the same location, resulting in traffic jams arising from physical crowding. Such local traffic jams at actin‐rich regions are likely to be a general feature of axonal transport since they also occur in Drosophila neurons. Repeated touch stimulation of C. elegans reduces the density of stationary pre‐SVs, indicating that these traffic jams can act as both sources and sinks of vesicles. This suggests that vesicles trapped in actin‐rich regions are functional reservoirs that may contribute to maintaining robust cargo flow in the neuron. A video abstract of this article can be found at: Video S1 ; Video S2 Abstract : Actin‐rich regions in axons act as hotspots where moving cargo stall. Stationary cargo at these locations enhances stalling of incoming cargo. Instead of forming permanent traffic jams, vesicles both stall as well as emerge from stationary vesicle clusters in a motor and neuronal activity‐dependent manner thus acting as dynamic reservoirs (http://onlinelibrary.wiley.com/doi/10.1111/tra.12544/suppinfo ).